Biomarkers of subclinical inflammation and increases in glycaemia, insulin resistance and beta-cell function in non-diabetic individuals: the Whitehall II study. Issue 5 (November 2016) - Herder, Christian; Færch, Kristine; Carstensen-Kirberg, Maren; Lowe, Gordon D; Haapakoski, Rita; Witte, Daniel R; Brunner, Eric J; Roden, Michael; Tabák, Adam G; Kivimäki, Mika; Vistisen, Dorte
Abstract : Objective: Higher systemic levels of pro-inflammatory biomarkers and low adiponectin are associated with increased risk of type 2 diabetes, but their associations with changes in glycaemic deterioration before onset of diabetes are poorly understood. We aimed to study whether inflammation-related biomarkers are associated with 5-year changes in glucose and insulin, HbA1c, insulin sensitivity and beta-cell function before the diagnosis of type 2 diabetes and whether these associations may be bidirectional. Design and methods: We used multiple repeat measures (17 891 person-examinations from 7683 non-diabetic participants) from the Whitehall II study to assess whether circulating high-sensitivity C-reactive protein (hsCRP), interleukin-6 (IL6), IL1 receptor antagonist (IL1Ra) and adiponectin are associated with subsequent changes in glycaemia, insulin, insulin resistance and beta-cell function (based on oral glucose tolerance tests). We examined bidirectionality by testing if parameters of glucose metabolism at baseline are associated with changes in inflammation-related biomarkers. Results: Higher hsCRP and IL6 were associated with increases in fasting insulin, insulin resistance and, for IL6, with beta-cell function after adjustment for confounders. Higher adiponectin was associated with decreases in fasting glucose, HbA1c, fasting insulin, insulin resistance and beta-cell function. The reverse approach showed that 2-h glucose and insulin sensitivity were associated with changes in IL1Ra. Fasting insulin and insulin resistance showed inverse associations with changes in adiponectin. Conclusions: Subclinical inflammation is associated with development of increased glycaemia, insulin resistance and beta-cell function in non-diabetic individuals. These findings are consistent with the hypothesis that inflammation-related processes may increase insulin resistance and lead to a compensatory upregulation of beta-cell function.